Organizational governance to integrate sustainability projects: a case study - Ghosh, Saumyendu; Buckler, Lauren; Skibniewski, Mirosław J.; Negahban, Sam; Kwak, Young Hoon (Technological and Economic Development of Economy, 2014)
Sustainable development represents a major challenge of the 21st century. Organizations use projects to implement strategic corporate objectives, exploring sustainable development from a project management perspective is imperative. While current project management techniques are well defined in terms of content and process to manage the budget-scope-time constraint, availability of organization resources and ability to adopt project governance strategies in a changing business environment, like incorporating sustainability in business process is ambiguous, literature has not explored how to cope with a normative situation like sustainability. We consider Small-to-Mid-Size-Construction-Organizations (SMSCOs), which makes up the largest portion of the project-based industry and are most impacted by new government regulations, as our population of interest. This paper addresses two primary objectives in relation to organizational resources available for SMSCOs: to identify an organization’s shortcomings in undertaking a sustainable project, and to identify means for improving organizational readiness to cope with governance of sustainable projects. A case study with a SMSCO to understand activities, resource availability, and how to improve organization readiness to undertake projects related to sustainability is discussed. A conceptual framework is presented for the adoptive project governance process to ensure resource constrained organizations like SMSCO’s can align better to govern such projects. First published online: 28 Jan 2014